Srikandi Lintas Iman: Upaya Melawan Intoleransi Beragama di Yogyakarta - Sa'idah, Zahrotus (PALASTREN: Jurnal Studi Gender, 2020)
Intolerance has always become serious problem recently, it happens both nationally and internationally.  In Indonesia, some intolerance actions have been found in big cities, including Yogyakarta. The existence of Srikandi Lintas Iman (SRILI) which consists of some active women attempts to fight against intolerance movements in Yogyakarta. This community emerged in Yogyakarta and has been supported by various popular organizations in Yogyakarta’s region, such as Nasyiatul Aisyiyyah, Fatayat NU, and Wanita Katolik Indonesia. Generally, this community stands as a specific organization for various interfaith women who had experienced social conflict. This research tries to focus on how SRILI can fight against religious intolerance in Yogyakarta and how effective is it to deal with this issue.This research uses qualitative approach combined with communication and sociological studies as its perspective. Hopefully, by using both sciences, social phenomenon in Indonesia, particularly ones that relate to how SRILI can deal with those intolerance issues in Yogyakarta can be resolved. The result of this observation as well as questions hopefully can answer on how far SRILI’s contribution as well as effectiveness on dealing with intolerance in Yogyakarta.